In-vitro anti-acne activity of Teucrium oliverianum methanolic extract against Cutibacterium acnes - Al-Ghanayem, Abdullah A. (Frontiers in Pharmacology, 2024)
Background: Acne vulgaris is a skin infection widely seen in adolescents between 10-19 years with males affected more than females. It mainly affects the face but may also affect the back and chest. The symptoms vary with mild acne manifesting as comedones and moderate acne as inflammatory lesions (papulopustular), nodules, and mild scarring while severe acne has the same symptoms that have not subsided within 6 months of treatment. Various treatments including topical medications containing different antibiotics are used to treat acne. Recently, herbal treatments have been shown as better alternatives to conventional treatment. Teucrium oliverianum Ging. ex Benth (Lamiaceae) is traditionally used for skin infections such as wound healing and biofilm formation. Methodology: Methanolic extract of T. oliverianum was subjected to liquid chromatography-mass spectrometry (LC-MS) analysis, and its antibacterial effect against C. acnes. The anti-acne, antiinflammatory, and antioxidant effects were also assessed using HaCaT cells infected with C. acnes. The cytotoxicity of the extract was evaluated using a neutral red uptake assay, and anti-inflammatory effects were determined by measuring TNF-α, IL-1β, INF-, and COX2 inhibition. The antioxidant action was assessed by ROS generation in HaCaT cells infected with C. acnes. Results: LC-MS analysis of the extract showed the presence of 16 different metabolites with L-carnitine, esculin sesquihydrate, and gamma-linoleic acid as major metabolites. The methanolic extract of T. oliverianum showed an antibacterial effect against C. acnes with an IC50 value of 263.2 µg/ml. The extract attenuated the cytotoxicity of C. acnes on the HaCaT cell and the IC50 was found to be 676.2 µg/ml. It also decreased dose-dependently the expression of TNF-, IL-1, INF-, and inhibited COX2 in the HaCaT cells infected with C. acnes. It also decreased the generation of reactive oxygen species.The results support the use of T. oliverianum as an anti-acne agent but it possesses mild antibacterial action. It showed anti-inflammatory effects in HaCaT cells infected with C. acnes. It is also an effective antioxidant and decreased the generation of reactive oxygen species. Comparison of the anti-acne effects and adverse reactions of extract with other treatments will provide more insight into its clinical efficacy and toxicity.